The introduction of new medical devices in the public health service of a small region of Spain. (30th September 2020) - Arana Aragón, B; Gavrila, D; Fernández Gomez, V; Ferrandez Cámara, M J; Floris Martín, J A; García Córdoba, F; Quesada Torres, J A; Sabuco Tebar, E; Soria Aledo, V; Parra, P
Abstract: Issue: The introduction of health technologies could have a positive impact on the population's health. However, it also plays a significant role on the evolution of the sanitary budget. These circumstances have promoted the development of specific groups of experts in health technologies assessment under the criteria of effectiveness, safety and efficiency. Description of the Problem: The main goal of Murcia Health Service is to guarantee the health of its population through an optimal use of resources. New medical devices(MD)need to be evaluated prior to their use in medical practice. HTA reports published by international and national agencies are not covering the growing and accelerated offer and demand of new MD Results: A technical group in charge of the evaluation of new MD requests (GTESIDS)was created in 2014. The group consists of 12 part-time collaborators of different health professions. During 2019, GTESIDS received 69 requests of evaluation, two thirds of which from surgical specialties, mainly general(11), orthopedic(10)and ophthalmic(7)surgery. GTESIDS advised to incorporate 23 and not to incorporate 26 MD, while 20 were still being evaluated as of February 29, 2020. The mean time GTESIDS needed to reach a conclusion and emit a recommendation was 151 days. We have found a published HTA report for only one of the MD evaluated. Lessons: HTA reports published by international and national agencies are rarely available and need to be adapted to the local framework. The GTESIDS scope would improve with a better resource allocation that will allow a more thorough and rapid evaluation. Key messages: HTA reports are not covering the growing offer of new medical device. The experience in Murcia has taught us the need to strengthen an actual collaboration between agencies.